2008
DOI: 10.1583/08-2424.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Wall Motion and Dynamic Geometry of the Inferior Vena Cava Using Intravascular Ultrasound:Implications for Future Device Design

Abstract: In the supine position, the IVC is elliptical and deforms anisotropically during the normal respiratory cycle. The greatest displacement (36%) is in the short axis during a Valsalva maneuver. These profound changes within the venous system will require intracaval devices to have active fixation to prevent migration. Devices should be designed to accommodate these changes to prevent fatigue failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 14 publications
0
15
1
Order By: Relevance
“…It should be noted that measurement of tilting in our study was done using a tube with 26 mm × 21 mm dimensions, which corresponds to the maximum dimensions measured during normal respiratory cycles and Valsalva maneuvers [11]. The influence of the caval diameters less than 21 mm or greater than 26 mm on the measurement of tilting is unknown.…”
Section: Discussionmentioning
confidence: 95%
“…It should be noted that measurement of tilting in our study was done using a tube with 26 mm × 21 mm dimensions, which corresponds to the maximum dimensions measured during normal respiratory cycles and Valsalva maneuvers [11]. The influence of the caval diameters less than 21 mm or greater than 26 mm on the measurement of tilting is unknown.…”
Section: Discussionmentioning
confidence: 95%
“…This is especially true with regard to IVC, and this phenomenon is minor in iliac veins as long as the venous pressure is adequate. 9,10 That is why to establish its real diameter to guide angioplasty balloon and stent selection, a CLD derived from CSA was calculated in this study. Based on the present studies, the following reference diameters should be considered: 18 mm for IVC, 16 mm for LCIV in men and 15 mm in women, 15 mm for RCIV in men and 14 mm for RCIV in women and 14 mm for EIVs in men and 13 mm in women.…”
Section: Discussionmentioning
confidence: 99%
“…Also, caliber changes are larger in veins than arteries. Murphy et al (7) reported that the inferior vena cava deforms during the normal respiratory cycle. Its diameter significantly increased with the Valsalva maneuver from 14.3 ± 4.1 to 19.6 ± 1.2 mm in the short axis and the vessel became approximately 40% larger during this maneuver.…”
Section: Discussionmentioning
confidence: 99%